MIIND : A Model-Agnostic Simulator of Neural Populations - Osborne, Hugh; Lai, Yi Ming; Lepperød, Mikkel Elle; Sichau, David; Deutz, Lukas; de Kamps, Marc (Frontiers in Neuroinformatics, 2021)
MIIND is a software platform for easily and efficiently simulating the behaviour of interacting populations of neurons governed by any 1D or 2D dynamical system. The simulator is entirely agnostic to the underlying neuron model of each population and provides an intuitive method for controlling the amount of noise which can significantly affect the overall behaviour. A network of populations can be set up quickly and easily using MIIND’s XML-style simulation file format describing simulation parameters such as how populations interact, transmission delays, post-synaptic potentials, and what output to record. During simulation, a visual display of each population’s state is provided for immediate feedback of the behaviour and population activity can be output to a file or passed to a Python script for further processing. The Python support also means that MIIND can be integrated into other software such as The Virtual Brain. MIIND’s population density technique is a geometric and visual method for describing the activity of each neuron population which encourages a deep consideration of the dynamics of the neuron model and provides insight into how the behaviour of each population is affected by its neighbourhood. By utilising GPU architecture, MIIND performs comparably or better than current direct simulation solutions for large population networks. It can be used to build neural systems that bridge the scales between an individual neuron model and a population network. This allows researchers to maintain a plausible path back from mesoscopic to microscopic scales while minimising the complexity of managing large numbers of interconnected neurons. In this paper, we introduce the MIIND system, its usage, and provide implementation details where appropriate.